Distribution of carabid beetles in agroecosystems across spatial scales - A review - Gongalsky, Konstantin B.; Cividanes, Francisco J. [UNESP] (My University, 2008)
The review focuses on the questions (1) how does the spatial heterogeneity of landscape influences carabid biodiversity, and (2) what are the main factors causing this biodiversity across nested spatial scales (study point - plant association - landscape level). The analysis of recent literature indicates that the spatial distribution of carabids differs at various spatial scales, and the factors responsible for the distribution are different. At the study point level most of the communities exhibit high variability of population density and diversity, which has no correlations with soil, and sometimes, vegetation, parameters. Most of the factors that contribute to formation of the communities are stochastic, simply because patches of a factor are much smaller than the size of a distinct carabid community. At the level of plant association, soil factors begin to play the role in driving the communities. At this level, litter depth, micro-climate and vegetation composition are the main factors. At the landscape level, geological factors, such as topography, landscape geochemistry, and history are playing important roles. As a conservation measure, spatial heterogeneity should be kept at all spatial scales at the same time to maintain carabid biodiversity in agricultural areas.
Keywords: Biodiversity; agroecosystems; Carabidae; Geostatistics; Habitat fragmentation; Spatial distribution; Species loss; agricultural ecosystem; beetle; biodiversity; climate effect; habitat fragmentation; heterogeneity; microclimate; population density; spatial distribution; spatial variation; species diversity; vegetation; Coleoptera